A NUMERICAL SIMULATION TO DETERMINE THE BEHAVIOR OF THE HYDROGEN-NATURAL GAS MIXTURE IN DISTRIBUTION NETWORKS - Bogdan Andrei Ionete; Mihai Albulescu; Sorin Gal; Alexandra Damascan (Romanian Journal of Petroleum & Gas Technology)
This article presents the world energy situation, the importance of energy transition, and it further designates hydrogen as a potential replacement for natural gas. Moreover, the paper specifies that the energy transition will be carried out gradually, sustained by conventional resources. Hydrogen can be mixed with natural gasses in current networks, but additional risks must be considered. These risks prove to be minimal in the distribution sector if the hydrogen fraction is kept within acceptable limits, and if optimal operation and safety measures are enforced. The behavior of the hydrogen-natural gas mixture, also called HENG , is studied based on distinguishing the physical and chemical properties of hydrogen and natural gas. In order to analyze the true behavior of the mixture in a distribution network, a numerical simulation was undertaken, whose analysis shows that there is a tight connection between the concentration of hydrogen in the system, consumption, and linepack , and the operational limits of the network must be established based on these data. Knowing the behavior, strategies and regulations can be drafted in order to safely exploit natural gas-hydrogen distribution networks. However, every distribution network has its own particularities, which is why additional studies both at theoretical as well as practical level, performed on real distribution networks, are needed.